2005
DOI: 10.1111/j.0908-8857.2005.03406.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary calcium limits size and growth of nestling tree swallows Tachycineta bicolor in a non‐acidified landscape

Abstract: 2005. Dietary calcium limits size and growth of nestling tree swallows Tachycineta bicolor in a non-acidified landscape. Á/ J. Avian Biol. 36: 127 Á/134.Much previous research has focussed on the role of food supply in determining the growth and the survival of avian offspring. More recently, acid deposition in some ecosystems has demonstrated that in addition to energy, birds also need to acquire sufficient nutrients such as calcium to be successful. Whether procurement of adequate levels of calcium can limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 48 publications
(72 reference statements)
0
35
0
1
Order By: Relevance
“…For example, limiting access to important food resources can reduce the growth rate of nestlings (Dawson and Bidwell 2005) and alter song development in adults (Nowicki et al 2002). Hormones can have an effect as well; for example, corticosterone reduces the amount of pheomelanic coloration in developing barn owls Tyto alba .…”
Section: Effects Of Small Increases In Corticosterone Levels On Morphmentioning
confidence: 99%
“…For example, limiting access to important food resources can reduce the growth rate of nestlings (Dawson and Bidwell 2005) and alter song development in adults (Nowicki et al 2002). Hormones can have an effect as well; for example, corticosterone reduces the amount of pheomelanic coloration in developing barn owls Tyto alba .…”
Section: Effects Of Small Increases In Corticosterone Levels On Morphmentioning
confidence: 99%
“…feather growth) later in nestling development. It is also not surprising that neither rate of growth nor length of tarsus in this study was influenced by availability of dietary carotenoids, because avian skeletal growth is limited by the availability of other nutrients, namely calcium (Dawson and Bidwell 2005). Interestingly, however, a recent experimental study investigating the effects of blow flies on nestling performance in eastern bluebirds breeding in Pennsylvania did not report similar effects on tarsus growth in this species, despite considerably higher parasite loads in control nests relative to my study population (Hannam 2006).…”
Section: Control Carotenoidmentioning
confidence: 67%
“…Previous research by Jedlicka et al (2013) using different primer sets (LCO1490 and HCO2198) found isopteran DNA (Armadillium vulgare) in 12 out of 13 fecal samples from Western Bluebird nestlings in Napa and Sonoma County vineyards. Armadillium vulgare is a calcium-rich food source (Ouyang and Wright 2005) and consequently may be an important component of bluebird diets during the breeding season (Tilgar et al 1999, Dawson andBidwell 2005). Clarke et al (2014) show that ZBJ-ArtF1c and R2c primers used here do not provide good coverage for Isoptera, provide excellent coverage for both Diptera and Lepidoptera, and adequate coverage for Hemiptera, Orthoptera, Coleoptera, and Hymenoptera.…”
Section: Discussionmentioning
confidence: 95%